Cryoprotectant‐free high‐pressure cooling and dynamic nuclear polarization for more sensitive detection of hydrogen in neutron protein crystallography. Issue 8 (8th August 2018) - Tanaka, Ichiro; Komatsuzaki, Naoya; Yue, Wen-Xue; Chatake, Toshiyuki; Kusaka, Katsuhiro; Niimura, Nobuo; Miura, Daisuke; Iwata, Takahiro; Miyachi, Yoshiyuki; Nukazuka, Genki; Matsuda, Hiroki
Abstract : To improve the sensitivity of hydrogen detection using neutrons, high‐pressure cooling of a relatively large protein single crystal and proton polarization of a protein polycrystalline state have been demonstrated as preliminary experiments. Abstract : To improve the sensitivity of hydrogen detection using neutrons, a proton‐polarization technique together with a high‐pressure cooling method is necessary. The highest pressure (200 MPa) used in the experiment described here enabled relatively large protein crystals to be cooled without any cryoprotectants while retaining the protein structure, and it was confirmed that high‐pressure‐cooled crystals diffracted to nearly the same resolution as flash‐cooled small crystals soaked with cryoprotectants. Dynamic nuclear polarization was used as a proton‐polarization technique for protein crystals, and ∼300 mg polycrystalline protein doped with TEMPOL gave a maximum proton polarization of 22.3% at a temperature of 0.5 K in a 2.5 T magnetic field.